Pengabdian Kepada Sekolah Melalui Kegiatan Edu Expo and Market Days (P5P2RA) Untuk Meningkatkan Jiwa Kewirausahaan Siswa - Khusnul Fadilla; Hatta Sabri; Maulina, Meri; Alqifti, Cut Ria; Nurulliani, Hilda; Israwani (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2024)
The background of this research is to display the results of activities carried out in the Independent Learning Curriculum, namely the projects in the Pancasila Rahmatan lil'alamin Student Profile. The aim of the Edu EXPO and Market Days (P5P2RA) activity is to train students in entrepreneurial activities and creative activities, and to provide students with an understanding of the importance of entrepreneurial and creative education in today's era. The method used in this service is Participatory Action Research (PAR). PAR (Participatory Action Research) is a type of research that actively involves all relevant parties in studying ongoing actions (where their own experiences are the problem) in order to make changes and improvements in a better direction. In this activity, students are divided into 7 stands, where in each stand there are 3 classes that will fill the stand. At each stand, students are asked to sell a variety of food and drinks. Students will also sell craft items that have been made during Project activities from the Pancasila Student Profile. Apart from that, there were several students who displayed their talents, starting from tilawatil Qur'an, fashion shows, drama, paskibraka, drum band, syarhil, and many more. So based on this research, it can be concluded that the Edu EXPO and Market Days (P5P2RA) activities can help students understand the importance of entrepreneurship and can also build student enthusiasm so they can become creative and innovative students.